On the Concavity of the Consumption Function - Carroll, Christopher D.; Kimball, Miles S. (Econometrica, 1996)
At least since Keynes (1935), many economists have had the intuition that the marginal propensity to consume out of wealth declines as wealth increases. Nonetheless, standard perfect-certainty and certainty equivalent versions of intertemporal optimizing models of consumption imply a marginal propensity to consume that is unrelated to the level of household wealth. We show that adding income uncertainty to the standard optimization problem induces a concave consumption function in which, as Keynes suggested, the marginal propensity to consume out of wealth or transitory income declines with the level of wealth.